La extensión rural para la actividad ganadera en Colombia: legislación, desarrollos, brechas y oportunidades - Hurtado, Angie; Díaz, Manuel Francisco; Enciso, Karen; Burkart, Stefan (International Center for Tropical Agriculture, 2020)
How to improve the socioeconomic conditions of the producers and achieve a sustainable intensification of the cattle sector that is able to give continuity to projected increases in the demand for animal source food? Since the 1950s, formulas have been discussed and applied to answer this and similar questions. Among the multiple factors and elements that are traditionally used, this study highlights a constant in the equation: rural extension services. Although rural development does not go exclusively through extension work, it is a necessary condition to achieve progress in this matter: the creation of capacities in technical and economic matters regarding the pasture and animal management allows producers to get involved in the solution of problems they are affected by, and having these capacities allows stimulating, not only the adoption of more sustainable and productive technologies, but also a more rational use of the available resources. However, the documentation on the application of extension services in developing countries reveals the difficulties caused by multiple factors, including market failures, little participation of the private sector and the ineffectiveness of States with little capacity to reach the target population, among others (Cohen and Lemma, 2011). Nongovernmental organizations or the communities themselves are interesting alternative providers of these services, but they can also fail (Birner and Anderson, 2007). In recent decades, Colombia as an example for many other Latin American countries, has evidenced progress in planning processes, social interventions and a range of governance reforms. This includes democratization and decentralization of the different processes that include agricultural extension. These changes in governance and policies have led to an approach that seeks to improve service through greater participation of regions and departments, as well as private institutions and organizations. In this way, the objective of this work is to provide knowledge about the institutional evolution of rural extension in Colombia by identifying and analyzing those elements and processes that have culminated in the current configuration of extension services, understanding these as the processes aimed at institutional articulation that seek to promote the dynamics of innovation and value generation (Landini, 2016). The study is also about describing some case studies from the livestock sector, which were applied during the last decade with the aim of examining their development and the lessons learned that allow discussing more precise strategies for the near future.